2010
DOI: 10.1038/nmeth.1506
|View full text |Cite
|
Sign up to set email alerts
|

A human MAP kinase interactome

Abstract: Mitogen Activated Protein Kinase (MAPK) pathways form the backbone of signal transduction within the mammalian cell. Here, we apply a systematic experimental and computational approach to map 2,269 interactions between human MAPK-related proteins and other cellular machinery and to assemble these data into functional modules. A core network of 641 interactions is supported by multiple lines of evidence including conservation with yeast. Using siRNA knockdowns, we reveal that a significant number of novel inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
147
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(154 citation statements)
references
References 44 publications
4
147
1
2
Order By: Relevance
“…12 In addition, this study found that MBD5 and RAI1, along with FMR1, are involved in circadian and mTOR signaling pathways, both associated with sleep disturbance. 12 MBD5 appears to share molecular relationships with ASD-associated genes, including protein-binding relationships with FMR1, 31 APC, 32 and MEF2C 32 ( Figure 5). Further, based on our co-expression studies, haploinsufficiency of MBD5 results in dysregulation of other ASD-associated genes, including UBE3A (AS), RAI1 (SMS), TCF4 (PTHS), MEF2C (OMIM#613443), and FMR1 (FXS) ( Figure 5).…”
Section: Mbd5 Functions In Transcriptional Regulationmentioning
confidence: 99%
“…12 In addition, this study found that MBD5 and RAI1, along with FMR1, are involved in circadian and mTOR signaling pathways, both associated with sleep disturbance. 12 MBD5 appears to share molecular relationships with ASD-associated genes, including protein-binding relationships with FMR1, 31 APC, 32 and MEF2C 32 ( Figure 5). Further, based on our co-expression studies, haploinsufficiency of MBD5 results in dysregulation of other ASD-associated genes, including UBE3A (AS), RAI1 (SMS), TCF4 (PTHS), MEF2C (OMIM#613443), and FMR1 (FXS) ( Figure 5).…”
Section: Mbd5 Functions In Transcriptional Regulationmentioning
confidence: 99%
“…These included 496 positive and 434 negative correlations between nuclear and mtDNA gene expression in CEU, plus 203 positive and 184 negative correlations in YRI. A total of 63 of these genes (29 positive and 34 negative) were found in common between CEU and YRI (Figure 2), including 15 ribosomal protein genes, ACIN1 (apoptotic chromatin condensation inducer protein activated by caspase-3, Figure 3a), and ZSWIM1 (zinc-finger SWIM domain-containing protein indirectly interacting with MT-ND2 through MAPK14, 35 Figure 3b). GO analyses indicated that positively-correlated nuclear genes were often involved in the regulation of transcription; those negatively-correlated were more likely to be involved in translation (for details, see Supplementary Table 2).…”
Section: Coordinated Expression Of Mtdna Genesmentioning
confidence: 99%
“…Previous studies support the utility of analyzing network interactions in receptorspecific pathways, to generate insights into signaling mechanisms. Furthermore, they also emphasized the potential of this approach for identifying new drug targets (Tu et al 2009;Astsaturov et al 2010;Bandyopadhyay et al 2010).…”
Section: Discussionmentioning
confidence: 99%